Numerical study and optimizing on cold plate splitter for lithium battery thermal management system. (25th February 2020) - Xu, Xiaoming; Tong, Guangyao; Li, Renzheng
Highlights: Add splitters into the straight channel to improve the thermal equilibrium of battery module. Use orthogonal experimental design method to research splitter structure parameters. Study the heat balance performance of the battery liquid cooling management system. Guide the design of battery thermal management. Abstract: In recent years, with vigorous promotion of the new energy vehicle industry, electric vehicle, as an important direction, has aroused widely attention. As one of the core parts of electric vehicles, the performance of power battery is greatly affected by temperature. On the basis of the summaries of main methods and research of battery thermal management, this paper uses FloEFD 2016 to simulate and study the thermal equilibrium performance of battery liquid cooling system through adding splitters into the straight channel. In order to improve the thermal equilibrium of battery module, this paper also uses orthogonal experimental design method to research 5 splitter structure parameters: splitter number, length, angle, the distance between two splitters and the offset distance. The results show that as the number of splitters increases, the average temperature difference of each cell decreases and also the deflection angle and length of splitters have a great influence on the thermal equilibrium performance of the battery pack.